Rare Orbital Myiasis in Post Exenteration Socket: A Case of Orbito Maxillary Mucormycosis: Doi: 10.36351/pjo.v40i1.1738 - Kakkar, Arushi; Bala, Madhu (Pakistan Journal of Ophthalmology, 2023)
We report a case of orbital Myiasis in post-exenteration socket in a 60-year-old diabetic female who was diagnosed with right orbito-maxillary mucormycosis and underwent exenteration and supra structure maxillectomy, seven years back. Turpentine oil packing and hydrogen peroxide wash was given followed by removal of the maggots with a blunt forceps. The collected maggots were stored in 10% formalin followed by maggot identification. Maggots were of blowfly species, Chrysomyabezziana. These maggots have a unique tendency to invade healthy tissues extensively besides necrotic tissues. This is probably a rare instance where orbital myiasis had occurred over the granulation tissue covering posterior orbital bones extending to the floor of the maxillary antrum. She was primarily treated with broad spectrum antibiotics, anti-parasitic agents followed by manual removal of the maggots subsequent to which the wound began to heal by secondary intention.